Using Leaf Ecological Stoichiometry to Direct the Management of Ligularia virgaurea on the Northeast Qinghai-Tibetan Plateau - Su, Haohai; Cui, Jiabao; Adamowski, Jan F.; Zhang, Xiaofang; Biswas, Asim; Cao, Jianjun (Frontiers in Environmental Science, 2022)
Leaf ecological stoichiometry not only reflects the plasticity and adaptability, but also the growth of plants within environments where temperature, precipitation, and soil properties vary across an elevation gradient. Ligularia virgaurea (Maxim.) Mattf. ex Rehder & Kobuski — an invasive poisonous plant — is common in the northeast portion of China’s Qinghai-Tibetan Plateau and its presence greatly affects the native ecosystem. Based on L. virgaurea leaf carbon ([C]leaf), nitrogen ([N]leaf) and phosphorus ([P]leaf) concentrations, and their ratios, the species’ coping strategies across an elevation gradient (2600 m, 3000 m, and 3300 m) were identified, and served to inform the development of improved management strategies. Mean [C]leaf, [N]leaf and [P]leaf in L. virgaurea across all elevations were 413.14 g·kg-1, 22.76 g·kg-1, and 1.34 g·kg-1, respectively, while [C]leaf : [N]leaf, [C]leaf : [P]leaf, and [N]leaf : [P]leaf were 18.27, 328.76, and 17.93. With an increase in precipitation and decrease in temperature from 2600 m to 3000 m to 3300 m, [C]leaf, [C]leaf : [N]leaf and [C]leaf : [P]leaf of L. virgaurea decreased at first and then increased. The [N]leaf and [P]leaf gradually increased, whereas [N]leaf : [P]leaf showed little change. Although temperature, precipitation and soil water content were the main factors affecting the ecological stoichiometry of L. virgaurea leaves, their roles in influencing leaf elements were different. The [C]leaf was mainly influenced by soil water content, [N]leaf by temperature and soil water content, and [P]leaf by all of them. With potential future climate change in the study area, L. virgaurea may grow faster than at present, although soil P may still be a growth-limiting element. As L. virgaurea can reduce plant diversity and the quality of forage, while increasing biomass, management of L. virgaurea should receive greater attention.